Production method of isostatic pressing graphite for semiconductors

By improving the raw materials and production processes of isostatic graphite, adding modified carbon fiber, graphene oxide and modified asphalt, and adopting a specific roasting process, the problems of insufficient flexural strength and low authenticity rate are solved, and the effects of high mechanical strength and high authenticity rate are achieved.

CN119797953APending Publication Date: 2025-04-11AOTONG CARBON (NEIJIANG) TECH CO LTD

Patent Information

Application Number
CN202510037098.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The flexural strength of existing isostatic graphite is insufficient, resulting in a low authenticity rate of the product, which is difficult to meet the semiconductor industry's requirements for high mechanical strength and high authenticity rate.

Method used

By improving the raw materials and production processes, specific steps include grinding, kneading, isostatic molding, calcining and graphitization. Modified carbon fibers and graphene oxide are added to the raw material, and the dispersion properties and binding strength of graphene oxide are improved by the combination of modified bitumen and chitosan. The roasting process uses step-type heating and iron covers to reduce cracks and improve uniformity.

Benefits of technology

The flexural strength and density of isostatic graphite have been significantly improved, and the authenticity rate of the product has been improved, achieving the goal of flexural strength not less than 73MPa, density not less than 1.81g/cm3 and authenticity rate not less than 92.5%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a production method of isostatic pressing graphite for a semiconductor, and belongs to the technical field of isostatic pressing graphite production. Comprising the following steps: S1, grinding: crushing coke and modified asphalt; the modified asphalt powder is obtained by modifying asphalt powder through chitosan; s2, mixing and kneading: firstly uniformly mixing coke, modified asphalt, modified carbon fiber and graphene oxide, and then adding the mixture into a mixing and kneading machine for mixing and kneading; the modified carbon fiber is obtained by firstly modifying carbon fiber with isocyanate, then impregnating with asphalt and graphitizing; s3, isostatic pressing molding; s4, roasting; and S5, graphitizing. By improving the raw materials in the prior art, the cracking rate of the product can be effectively reduced, the breaking strength of the product can be remarkably improved, meanwhile, the roasting time is remarkably shortened, the production period is effectively shortened, and the cost is saved. Specifically, the bending strength of the isostatic pressing graphite for the semiconductor prepared by the method is not lower than 73MPa, the rate of graded products is not lower than 92.5%, and the production requirements of the isostatic pressing graphite for the semiconductor are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of isostatic graphite production, in particular to a method for producing isostatic graphite for semiconductors. Background Art

[0002] Isostatic graphite is a high-performance special graphite material with electrical conductivity, high strength, high thermal conductivity and high uniformity. These characteristics make isostatic graphite an important material in the semiconductor industry. When isostatic graphite parts are used in the semiconductor industry, high performance requirements are placed on isostatic graphite in all aspects, such as density, mechanical strength, thermal expansion coefficient, etc.

[0003] The most important indicator of mechanical strength is flexural strength, which is closely related to the density of semiconductor graphite. At present, while requiring products to have higher mechanical flexural strength, they are bound to face the technical problem of low product authenticity rate. This is a prominent contradiction in the current high-end graphite production field.

[0004] Based on this, it is extremely important to provide a production method that can effectively improve the flexural strength of the product and effectively improve the product authenticity rate. Summary of the invention

[0005] The purpose of the present invention is to provide a method for producing isostatically pressed graphite for semiconductors for the first time, so as to at least achieve the purpose of improving the flexural strength and increasing the product authenticity rate.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for producing isostatically pressed graphite for semiconductors comprises the following steps:

[0008] S1. Grinding: crushing coke and modified asphalt; the modified asphalt is obtained by modifying asphalt with chitosan;

[0009] S2 kneading: first, the coke, modified asphalt, modified carbon fiber and graphene oxide are uniformly mixed, and then added to a kneading machine for kneading;

[0010] The modified carbon fiber is obtained by first modifying the carbon fiber with isocyanate, then impregnating it with asphalt and graphitizing it;

[0011] S3. Isostatic pressing;

[0012] S4. roasting;

[0013] S5. Graphitization.

[0014] As some possible implementation methods of the present application, in step S1, the coke and modified asphalt are crushed to have a particle size of 1 to 25 μm.

[0015] As some possible implementation methods of the present application, the added amount of the modified carbon fiber and the graphene oxide is 1% to 5%.

[0016] As some possible implementation methods of the present application, the added amount of the modified carbon fiber is 3%, and the added amount of the graphene oxide is 4%.

[0017] As some possible implementation modes of the present application, the carbon fiber has a diameter of 0.4 to 0.6 mm and a length of 0.8 to 1.1 mm.

[0018] As some possible implementation modes of the present application, the carbon fiber has a diameter of 0.5 mm and a length of 1 mm.

[0019] As some possible implementation methods of the present application, the roasting target temperature is 800-900° C., and in step S4, the roasting time is 30-40 days.

[0020] As some possible implementation methods of the present application, in step S4, the roasting is carried out in a step-by-step heating manner, and each stage is kept warm to balance the temperature difference between the inside and outside of the product; wherein the temperature rise curve of each stage during roasting is as follows:

[0021] 0~200℃, the heating rate is 18~20℃ / h; 200~600℃, the heating rate is 4~5℃ / h; 600℃~target temperature, the heating rate is 8~9℃ / h.

[0022] As some possible implementation methods of the present application, in step S4, the sheath selected for roasting is an iron sheath.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention can effectively reduce the crack rate of the product and significantly improve the flexural strength of the product by optimizing the raw materials of the isostatic graphite in the prior art and the relevant parameters in the production process. At the same time, on the basis of improving the raw materials, the roasting time can be significantly shortened (shortened by about half), thereby effectively saving the production cycle and saving costs. Specifically, the flexural strength of the isostatic graphite for semiconductors prepared by the method of the present invention is not less than 73MPa, and the density is not less than 1.81g / cm 3 The genuine rate is not less than 92.5%, which meets the production requirements of isostatic graphite for semiconductors. DETAILED DESCRIPTION

[0025] In the prior art, the raw materials of isostatic graphite are mostly coke and asphalt. The flexural strength of isostatic graphite prepared from the two is generally lower than 45Mpa, which is difficult to meet the production requirements of isostatic graphite for semiconductors, and thus has certain defects in actual implementation.

[0026] Based on this, the present invention provides a method for producing isostatically pressed graphite for semiconductors, comprising the following steps:

[0027] S1. Grinding: crushing coke and modified asphalt; the modified asphalt is obtained by modifying asphalt with chitosan;

[0028] S2 kneading: first, the coke, modified asphalt, modified carbon fiber and graphene oxide are uniformly mixed, and then added to a kneading machine for kneading;

[0029] The modified carbon fiber is obtained by first modifying the carbon fiber with isocyanate, then impregnating it with asphalt and graphitizing it;

[0030] S3. Isostatic pressing;

[0031] S4. roasting;

[0032] S5. Graphitization.

[0033] Among them, the preparation method of the modified asphalt is such as the preparation method of Example 1 in the patent application number 201810978977.9.

[0034] The preparation method of the modified carbon fiber is as follows:

[0035] (1) The first modified carbon fiber is prepared by referring to the method in Example 1 of patent application number CN201811544172.X; different from the patent, in the present invention, the diameter of the carbon fiber is 0.4-0.6 mm and the length is 0.8-1.1 mm.

[0036] (2) The first modified carbon fiber is embedded with asphalt powder and placed in an impregnation tank, and then the impregnation furnace is evacuated and inert gas is introduced, and then the impregnation furnace is heated to 300°C and kept warm for 1 hour, and then naturally cooled to room temperature; then the impregnation tank is taken out and placed in a carbonization furnace for carbonization, and the modified carbon fiber is obtained after cooling. The carbonization conditions are: the temperature is increased from room temperature to 250°C at 50°C / h and kept warm for 1 hour, and then the temperature is increased to 900°C at 20°C / h, and then kept warm for 1 hour. During the entire carbonization process, an inert gas with a pressure of 0.5 to 1 MPa is used for protection.

[0037] In the present invention, in order to effectively improve the flexural strength of isostatic graphite products, only carbon fibers are initially added to the raw materials (coke and asphalt). However, the surface of the carbon fibers has the characteristics of being hydrophobic, smooth, and porous, resulting in an extremely low interface bonding degree between the carbon fibers and the raw materials. This causes sand holes, voids, and even cracks to appear in the isostatic graphite during production, which seriously affects the density, uniformity, and authenticity of the product.

[0038] Based on this, the present invention modifies the carbon fiber twice, firstly, the carbon fiber is modified by isocyanate, so as to graft organic functional groups on the surface of the carbon fiber, improve its bonding degree and dispersion with asphalt, then impregnate it with asphalt, and graphitize it at high temperature, so that the gaps of the carbon fiber can be filled with pyrolytic carbon, the density of the carbon fiber is increased, the mechanical strength and density of the product are improved, and the physical and chemical compatibility with coke can be significantly improved. The graphitized carbon fiber can also reduce the deformation (volume shrinkage and expansion) of the baked blank during the graphitization process, reduce the probability of cracks in the graphite blank, and improve the genuine product rate.

[0039] Although the carbon fiber that has been modified twice has effectively improved its bonding degree with the raw materials and its dispersion in the raw materials to a certain extent, the final products are still uneven, and some products still have small cracks, which seriously affects the authenticity rate.

[0040] Based on this, the present invention adds graphene oxide to the modified carbon fiber, which can play a role in nucleation and growth inhibition for the formation of asphalt carbonaceous mesophase, effectively improve the density and mechanical strength of the product, and further improve the cracking of the product. Therefore, after adding graphene oxide, the flexural strength of the product can be further improved, and the rate of genuine products can be increased. Graphene oxide is a chemically treated oxide of graphene, in which oxygen-containing functional groups can affect the strength of the final graphite product, so the amount of addition needs to be strictly controlled to prevent the performance of isostatic graphite from being reduced.

[0041] However, graphene oxide is difficult to disperse effectively in asphalt, resulting in technical problems such as poor uniformity of the final product and the need to improve the authenticity rate.

[0042] Based on this, the present invention modifies asphalt with chitosan on the basis of graphene oxide. After the modification, chitosan is introduced into the modified asphalt. The functional groups such as hydroxyl groups contained in chitosan can form hydrogen bonds with the functional groups such as hydroxyl groups in graphene oxide, thereby significantly improving the bonding strength and dispersion performance of graphene oxide and modified asphalt, and effectively improving the technical problems of poor product uniformity and low authenticity rate.

[0043] In addition, after the asphalt is modified by chitosan, the viscosity of the binder can be increased during the coking stage of the binder, so that the intermediate phase formed by the asphalt does not have the conditions to form a sphere under the action of surface tension due to the increase in the viscosity of the system, thereby effectively inhibiting the growth of the asphalt intermediate phase and further improving the density and mechanical strength of the product.

[0044] In summary, the present invention can effectively improve the density, mechanical strength and product authenticity rate of the product by improving the raw materials of the prior art.

[0045] In order to further improve the authenticity rate of the product, as some feasible implementation methods of the present application, in step S1, the coke and modified asphalt are crushed to have a particle size of 1 to 25 μm.

[0046] In order to further improve the flexural strength of the product and increase the genuine rate of the product, as some of the implementable embodiments of this application, the amount of modified carbon fiber and graphene oxide added is limited, that is, the amount of modified carbon fiber and graphene oxide added is 1% to 5%. The amount of modified carbon fiber and graphene oxide added to the raw material is extremely important. If too little is added, it is difficult to play the role of improving the mechanical strength. If too much is added, it will have an adverse effect on other properties of the product, thereby reducing the genuine rate.

[0047] In order to further improve the flexural strength of the product and increase the authenticity rate of the product, as some feasible implementation methods of the present application, the addition amount of modified carbon fiber and graphene oxide is further limited, that is, the addition amount of the modified carbon fiber is 3%, and the addition amount of the graphene oxide is 4%.

[0048] In order to further improve the flexural strength of the product and increase the genuine rate of the product, as some of the implementable embodiments of this application, the specifications of the modified carbon fiber are limited, that is, the diameter of the carbon fiber is 0.4-0.6mm and the length is 0.8-1.1mm. In actual processing, if the length of the carbon fiber is too small, it is difficult to effectively improve the mechanical strength. If the length is too long, the crack degree of the product will increase, seriously affecting the genuine rate of the product.

[0049] In order to further improve the flexural strength of the product and increase the authenticity rate of the product, as some feasible implementation methods of the present application, the specifications of the modified carbon fiber are further limited, that is, the diameter of the carbon fiber is 0.5 mm and the length is 1 mm.

[0050] In order to further improve the authenticity rate of the product, as some feasible implementation methods of the present application, the maximum roasting temperature and the total roasting time are further limited, that is, the roasting target temperature is 800-900°C, and in step S5, the roasting time is 30-40 days.

[0051] The roasting process plays a relatively important role in the production process of isostatic graphite, and has a very important influence on the performance of the product (such as crack degree, mechanical properties, etc.). The present invention can effectively improve the quality rate of graphite products by limiting the maximum roasting temperature and roasting time. In addition, the present invention can shorten the roasting time by one third compared with the prior art by improving the raw materials of the prior art, thereby effectively improving the roasting efficiency.

[0052] In order to further improve the authenticity rate of the product, as some feasible implementation methods of the present application, the roasting temperature rise curve is further limited, that is, in step S4, the roasting is carried out in a step-by-step heating manner, and each stage is kept warm to balance the temperature difference between the inside and outside of the product; wherein the temperature rise curve of each stage during roasting is as follows:

[0053] 0~200℃, the heating rate is 18~20℃ / h; 200~600℃, the heating rate is 4~5℃ / h; 600℃~target temperature, the heating rate is 8~9℃ / h. The present invention adopts different heating rates for calcination at different stages, which can effectively reduce the generation of cracks and thus improve the product authenticity rate.

[0054] In order to further improve the quality rate of the product, as some of the embodiments of the present application, the material of the sheath is further limited, that is, in step S4, the sheath selected during roasting is an iron sheath (such as a steel sheath, etc., the following embodiments and comparative examples all use a steel sheath). The iron sheath contains iron, which will generate infrared radiation after being heated. After the radiation penetrates deeply into the roasted product, it can reduce the temperature difference between the inside and outside of the roasted product, thereby reducing the problem of roasting cracking of the roasted product, thereby improving the quality rate of the product. In addition, compared with other materials, the thermal conductivity of the steel sheath itself is relatively large, and the heat can be quickly homogenized to the surface of the blank, promoting uniform heat conduction to the product and improving product uniformity.

[0055] The production method of isostatic graphite for semiconductors described in the present application is further described in detail below in conjunction with specific implementation methods.

[0056] Example 1

[0057] S1. Grinding: Coke (with ash and sulfur content less than 0.5% and true density higher than 2.05g / cm 3 Calcined petroleum coke) and modified asphalt are crushed into powder with a particle size of 5 to 20 μm;

[0058] S2. Kneading: Mix coke, modified asphalt, modified carbon fiber (the diameter of the carbon fiber is in the range of 0.4 to 0.6 mm, and the length is in the range of 0.8 to 1.1 mm) and graphene oxide evenly, and then add them into a kneading machine for kneading; wherein the mass ratio of coke to modified asphalt is 2:1, the amount of modified carbon fiber added is 3.5%, and the amount of graphene oxide added is 2.5%.

[0059] S3. Isostatic pressing: The kneaded material is placed in an isostatic press to obtain a green embryo, wherein the molding temperature is 35° C., the molding pressure is 150 MPa, and the molding time is 15 min.

[0060] S4. Calcination: The green body obtained in S3 is placed in a calcination furnace, and is calcined for the first time under a nitrogen environment to obtain a first calcined body; the first calcined body is impregnated with asphalt, and the impregnation conditions are: 200°C, 5MPa, and 11h; the impregnated body is placed in a calcination kiln, and is calcined for the second time under a nitrogen environment to obtain a second calcined body.

[0061] The first and second roasting were carried out in a step-by-step heating mode, and each stage was kept warm for a period of time to balance the temperature difference between the inside and outside of the product; the heating curves of each stage of the first and second roasting are as follows: 0-200°C, heating rate of 20°C / h; 200-600°C, heating rate of 5°C / h; 600°C-900°C, heating rate of 9°C / h. The total duration of the two roastings was 37 days.

[0062] S5. Graphitization: The green body obtained by the second calcination is placed in a graphitization furnace and graphitized at 3000°C for 20 days to obtain isostatic graphite.

[0063] After testing, the flexural strength of the isostatically pressed graphite prepared in Example 1 is 73 MPa and the density is 1.81 g / cm 3 , the authenticity rate is 92.5%.

[0064] Example 2

[0065] Compared with Example 1, only the addition amounts of modified carbon fiber and graphene oxide were adjusted, and the remaining steps and parameters were the same as those in Example 1.

[0066] The adjusted addition amounts are: 3% of the modified carbon fiber and 4% of the graphene oxide.

[0067] The total roasting time of this embodiment is 36 days.

[0068] After testing, the flexural strength of the isostatically pressed graphite prepared in Example 2 is 75 MPa and the density is 1.82 g / cm 3 , the authenticity rate is 93.1%.

[0069] Example 3

[0070] Compared with Example 2, only the diameter and length of the carbon fiber are adjusted, and the length and diameter of the modified carbon fiber are further limited. The remaining steps and parameters are the same as in Example 1.

[0071] After adjustment, the diameter of the carbon fiber is 0.5 mm and the length is 1 mm.

[0072] The roasting time is 34 days.

[0073] After testing, the flexural strength of the isostatically pressed graphite prepared in Example 3 is 80 MPa and the density is 1.85 g / cm 3 , the authenticity rate is 94.2%.

[0074] Comparative Example 1

[0075] Compared with Example 1, the carbon fiber is not modified, and the remaining steps and parameters are the same as Example 1.

[0076] The roasting time is 36 days.

[0077] After testing: the flexural strength of the isostatically pressed graphite prepared in Comparative Example 1 is 63 MPa.

[0078] It can be seen that in this comparative example, even if carbon fiber, graphene oxide and chitosan are added, it is difficult for the carbon fiber to be evenly dispersed in other raw materials without modifying the modified carbon fiber, and it is difficult to form a good bonding force with other raw materials, which leads to a significant decrease in flexural strength compared with Examples 1 to 3. At the same time, because the carbon fiber is not modified, cracks appear on the surface of the prepared finished product, which seriously affects the authenticity rate, which is 57%.

[0079] Comparative Example 2

[0080] Compared with Example 1, graphene oxide is not added, and the remaining steps and parameters are the same as Example 1.

[0081] The roasting time is 38 days.

[0082] After testing: the flexural strength of the isostatically pressed graphite prepared in Comparative Example 2 is 64.5 MPa.

[0083] It can be seen that in this comparative example, even if modified carbon fiber and chitosan are added, without adding graphene oxide, the flexural strength of the product is still lower than that of Examples 1-3; at the same time, cracks will appear on the surface of the product, affecting the authenticity rate, which is 78%.

[0084] Comparative Example 3

[0085] Compared with Example 1, the asphalt is not modified, and the remaining steps and parameters are the same as Example 1.

[0086] The roasting time is 39 days.

[0087] After testing: the flexural strength of the isostatically pressed graphite prepared in Comparative Example 3 is 67 MPa.

[0088] It can be seen from this that in this comparative example, since chitosan was not added to the raw materials, the mechanical strength was reduced. At the same time, it was difficult for graphene oxide to form hydrogen bonds with the functional groups in chitosan, resulting in a reduction in the dispersion of graphene oxide in asphalt and the degree of bonding with asphalt, which in turn led to a reduction in the uniformity of the product. At the same time, it also caused a certain degree of cracks on the surface of the product, affecting the authenticity rate, which was 82%.

[0089] Comparative Example 4

[0090] Compared with Example 1, only coke and asphalt are added as raw materials, and the remaining steps and parameters are the same as Example 1.

[0091] The roasting time is 75 days.

[0092] After testing: the flexural strength of the isostatically pressed graphite prepared in Comparative Example 4 is 44 MPa, and the genuine rate is 84%.

[0093] It can be seen from this that: the comparative example uses raw materials of the prior art, and the flexural strength of the product obtained is low; but at the same time, because no additional filler is added to the raw materials, the crack degree of the product can be effectively reduced, making the authenticity rate relatively high.

[0094] The criteria for judging genuine products are as follows: (1) There are no cracks on the surface of the product, including but not limited to cross cracks, side cracks, web cracks, etc.; (2) The product has no damage or falling pieces, and the size of the baked billet is larger than the size specified by the brand.

[0095] In summary, the flexural strength of the isostatically pressed graphite prepared in Examples 1-3 is not less than 73 MPa, and the density is not less than 1.81 g / cm 3 The flexural strength and authenticity rate are not less than 92.5%, which are significantly higher than those of the products in Comparative Example 1 (flexural strength 63MPa, authenticity rate 57%), Comparative Example 2 (flexural strength 64.5MPa, authenticity rate 78%), Comparative Example 3 (flexural strength 67MPa, authenticity rate 82%) and Comparative Example 4 (flexural strength 44MPa, authenticity rate 84%), meeting the production requirements of isostatic graphite for semiconductors.

Claims

1. A method for producing isostatically pressed graphite for semiconductors, characterized in that: The steps include: S1. Grinding: crushing coke and modified asphalt; the modified asphalt is obtained by modifying asphalt with chitosan; S2 kneading: first, the coke, modified asphalt, modified carbon fiber and graphene oxide are uniformly mixed, and then added to a kneading machine for kneading; The modified carbon fiber is obtained by first modifying the carbon fiber with isocyanate, then impregnating it with asphalt and graphitizing it; S3. Isostatic pressing; S4. roasting; S5. Graphitization.

2. The method for producing isostatically pressed graphite for semiconductor according to claim 1, characterized in that: In step S1, the coke and modified asphalt are crushed to have a particle size of 1 to 25 μm.

3. The method for producing isostatically pressed graphite for semiconductor according to claim 1, characterized in that: The added amount of the modified carbon fiber and the graphene oxide is 1% to 5%.

4. The method for producing isostatically pressed graphite for semiconductor according to claim 3, characterized in that: The added amount of the modified carbon fiber is 3%, and the added amount of the graphene oxide is 4%.

5. The method for producing isostatically pressed graphite for semiconductor according to claim 1, characterized in that: The carbon fiber has a diameter of 0.4-0.6 mm and a length of 0.8-1.1 mm.

6. The method for producing isostatically pressed graphite for semiconductor according to claim 5, characterized in that: The carbon fiber has a diameter of 0.5 mm and a length of 1 mm.

7. The method for producing isostatically pressed graphite for semiconductor according to claim 1, characterized in that: In step S4, the target calcination temperature is 800-900°C, and the calcination time is 30-40 days.

8. The method for producing isostatically pressed graphite for semiconductor according to claim 7, characterized in that: In step S4, the roasting is performed in a step-by-step heating manner, and each stage is kept warm to balance the temperature difference between the inside and outside of the product; wherein the temperature rise curve of each stage during roasting is as follows: 0~200℃, the heating rate is 18~20℃ / h; 200~600℃, the heating rate is 4~5℃ / h; 600℃~target temperature, the heating rate is 8~9℃ / h.

9. The method for producing isostatically pressed graphite for semiconductor according to claim 1, characterized in that: In step S4, the sheath selected for roasting is an iron sheath.

Citation Information

Patent Citations

  • Preparation method of ultrafine-structured isostatic pressing formed graphite

    CN108793151A

  • Isocyanate surface modified carbon fiber-polypropylene composite material and preparation method thereof

    CN109810414A

Cited By

  • Preparation method of carbon fiber toughened graphite throat liner material

    CN122212781A